2019
DOI: 10.21161/mjm.180213
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro antileptospiral activity of Canarium odontophyllum Miq. (Dabai) leaves extract

Abstract: Aims: To evaluate the anti-leptospiral activity of Canarium odontophyllum leaves against Leptospira interrogans serovar Bataviae and Leptospira borgpetersenii serovar Javanica. Methodology and results: The extracts (hexane, acetone, methanol and aqueous) used in this study were tested at concentration ranging from 0.049 mg/mL to 25 mg/mL using broth microdilution method. Percentage inhibition (%) was obtained through OD reading at 400 nm. Only methanol extract was incubated with Leptospira to observe populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Arulmozhi et al investigated the ethanolic extract of Andrographis paniculata (commonly known as creat or green chiretta) leaves and found it to possess spirocidal activity against various Leptospira species, suggesting its potential as an alternative treatment option ( Natarajaseenivasan, 2017 ). Similarly, Ishak et al (2019) reported the spirocidal activity of extracts from Canarium odontophyllum (locally known as dabai in Sarawak and kembayau in Sabah and Brunei) leaves against Leptospira , highlighting the therapeutic potential of natural remedies.…”
Section: Newly Synthesized/natural Compounds Of Spirocidal Agentsmentioning
confidence: 96%
“…Arulmozhi et al investigated the ethanolic extract of Andrographis paniculata (commonly known as creat or green chiretta) leaves and found it to possess spirocidal activity against various Leptospira species, suggesting its potential as an alternative treatment option ( Natarajaseenivasan, 2017 ). Similarly, Ishak et al (2019) reported the spirocidal activity of extracts from Canarium odontophyllum (locally known as dabai in Sarawak and kembayau in Sabah and Brunei) leaves against Leptospira , highlighting the therapeutic potential of natural remedies.…”
Section: Newly Synthesized/natural Compounds Of Spirocidal Agentsmentioning
confidence: 96%